Unlocking Resilience: Investigating the Impact of Childhood Trauma on Academic Achievement and Exploring Innovative Strategies for Support - Dr. Samia Mazhar; Dr. Sameena Iqbal; Maria Tanvir; Dr. Amna Hassan (Review Journal of Social Psychology & Social Works, 2025)
This research investigates the impact of childhood trauma on academic achievement among students in Pakistan and explores innovative strategies for supporting affected students. Using a mixed-methods approach, the study combined quantitative surveys, qualitative interviews with educators, school counselors, and parents, and archival school data. The findings indicated a significant negative correlation between trauma exposure and academic performance, with rural students being particularly affected. The study also revealed that schools lack trauma-informed practices and that emotional and behavioral challenges hinder students’ academic success. Based on these insights, the study recommends the introduction of trauma-informed teaching, mental health services, and parent education.